Analisis Determinan Harga Saham: Peran RasioPasar dan Nilai Buku Ekuitas pada Sektor Pertambangan 2021–2024Analisis Determinan Harga Saham: Peran RasioPasar dan Nilai Buku Ekuitas pada Sektor Pertambangan 2021–2024 - Rachmat Rinaldi; Djeni Indrajati Widjaja (Ikatan Da'i Indonesia, 2026)
Fundamental analysis through financial ratios remains a critical tool for investors navigating the high-volatility environment of commodity-based equity markets. This study investigates the extent to which Earnings Per Share (EPS) and Book Value Per Share (BVPS) contribute to stock price formation among mining companies listed on the Indonesia Stock Exchange (IDX) over the 2021–2024 observation period. Employing a causal-quantitative design with multiple linear regression, this study analyzed 72 firm-year observations drawn from 18 selected companies through purposive sampling. Statistical estimation confirms that EPS exerts a positive and significant influence on stock prices (t = 6.101; p = 0.001), and BVPS similarly demonstrates a positive and significant effect (t = 3.097; p = 0.003). The joint significance test further validates that both variables collectively explain stock price movements. These results reinforce the signaling role of fundamental financial information in commodity equity valuation, underscoring the importance of earnings quality and net asset strength as investor decision drivers.